An Updated Review on Synthesis and Biological Activities of Thiosemicarbazide Analogs: A Review - Kumar, Akhalesh; Mishra, Rakhi; Mazumder, Avijit; Mazumder, Rupa; Kumar, Arun (Asian Journal of Chemistry, 2021)
This review paper focuses on the different synthetic methodologies that researchers have adopted to synthesize various thiosemicarbazide derivatives with different biological activities of synthesized compounds in the last 20 years. Most of the investigations available in the literature are directed to the biological activities of thiosemicarbazide derivatives with less discussion on its synthetic schemes. This review article presents various reaction scheme, which has been adopted for thiosemicarbazide derivative synthesis along with the reported pharmacological activities of synthesized analogs. The available literature in the article aims to encourage more studies on the synthesis of thiosemicarbazide derivatives, which will help for drug discovery having thiosemicarbazide nucleus.